2021
DOI: 10.1007/s13721-021-00301-x
|View full text |Cite
|
Sign up to set email alerts
|

Binding ability of arginine, citrulline, N-acetyl citrulline and thiocitrulline with SARS COV-2 main protease using molecular docking studies

Abstract: In this article, the binding abilities of arginine, citrulline, N -acetyl citrulline and thiocitrulline on the active sites of SARS-COV-2 protease have been investigated using in-silico studies. All the above ligands bind selectively and preferentially to Cys-145 active site and also to other amino acids surrounding to it in the main protease. Of which arginine forms less number of weaker bonds compared to the other ligands, it by itself is a precursor for the formation of citrulline ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…A clinical study containing 60 COVID-19 patients indicates that oral supplementation of l-glutamine at the early stage shorten the hospital stay and reduced the need for ICU, [26] which is consistent with our observations that l-glutamine administration prolonged the survival of coronavirus-infected mice. In addition, it has been investigated that l-citrulline could bind to the active sites of SARS-COV-2 protease, [81] which reveals the possible mechanism used by l-citrulline to defend against SARS-CoV-2. More importantly, we found that combined supplementation of l-citrulline and l-glutamine could improve disease outcomes than the alone administration of l-citrulline or l-glutamine.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study containing 60 COVID-19 patients indicates that oral supplementation of l-glutamine at the early stage shorten the hospital stay and reduced the need for ICU, [26] which is consistent with our observations that l-glutamine administration prolonged the survival of coronavirus-infected mice. In addition, it has been investigated that l-citrulline could bind to the active sites of SARS-COV-2 protease, [81] which reveals the possible mechanism used by l-citrulline to defend against SARS-CoV-2. More importantly, we found that combined supplementation of l-citrulline and l-glutamine could improve disease outcomes than the alone administration of l-citrulline or l-glutamine.…”
Section: Discussionmentioning
confidence: 99%